The regulatory and Health Technology processes in Europe and drug market access. The case of cystic fibrosis - Latorre Martinez, Mayra; Serrano, Pedro; Sarria Santamera, Antonio (Farmeconomia. Health Economics and Therapeutic Pathways, 2015)
In order to reach the European market, a new drug needs to receive a positive evaluation regarding its quality, safety and efficacy by regulatory health authorities and also obtain a positive HTA appraisal regarding its cost-effectiveness by HTA bodies. Regulators and HTA bodies are collaborating in several projects at European level in order to harmonize the scientific requirements of both evaluations to the maximum extent possible. The comparison of the regulatory evaluation performed by EMA for Kalydeco and the HTA appraisals issued by several EU bodies exemplifies the dilemma between scientific evidence and local economic considerations and the difficulties in the achievement of harmonization and therefore equity in the access to drugs.